Pengaruh berbagai sumber pengasapan terhadap kadar protein, mikrobiologis dan organoleptik ikan nila (Oreochromis niloticus) asap - Abdul Hadi; Wiqayatun Khazanah; Andriani Andriani; Husna Husna (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2022)
One of the processes of smoking fish is using organic materials. Smoking also gives a good flavor and aroma. Smoked fish can be consumed directly and also processed further. The study aimed to measure the effect of various smoke sources on microbiological, organoleptic and protein levels of smoked tilapia. The research design was experimental with a Randomized Control Trial (RCT) using coconut husk, rice husk, and bamboo leaf smoke sources. The research was conducted at the Organoleptic Laboratory of the Department of Nutrition, Health Polytechnic of Aceh, Ministry of Health, in 2021. Fish smoking uses three smoke sources burning coconut fiber, bamboo leaves and rice husks in aluminum smoke tubes. Microbiological tests and protein content in the Laboratory of the Balai Pengujian dan Sertifikasi Mutu Barang (BPSMB). Data analysis using ANOVA and Duncan tests at 95% CI. The results showed that smoking tilapia with three smoke sources had a significant effect on color, taste and aroma and protein content (p<0,05) but had no significant effect on texture and microbial count of smoked tilapia (p>0,05). In conclusion, rice husk smoked tilapia was most preferred in terms of color, taste, texture and aroma. Coconut husk smoked tilapia has the highest protein content and lowest microbial count.